Quality of urban climate adaptation plans over time - Diana Reckien; Attila Buzasi; Marta Olazabal; Niki-Artemis Spyridaki; Peter Eckersley; Sofia G. Simoes; Monica Salvia; Filomena Pietrapertosa; Paris Fokaides; Sascha M. Goonesekera; Léa Tardieu; Mario V. Balzan; et al. (npj - Urban Sustainability, 2023)
Defining and measuring progress in adaptation are important questions for climate adaptation science, policy, and practice. Here, we assess the progress of urban adaptation planning in 327 European cities between 2005 and 2020 using three `ADAptation plan Quality Assessment' indices, called ADAQA-1/ 2/ 3, that combine six plan quality principles. Half of the cities have an adaptation plan and its quality significantly increased over time. However, generally, plan quality is still low in many cities. Participation and monitoring and evaluation are particularly weak aspects in urban adaptation policy, together with plan `consistency'. Consistency connects impacts and vulnerabilities with adaptation goals, planned measures, actions, monitoring and evaluation, and participation processes. Consistency is a key factor in the overall quality of plans. To help evaluate the quality of plans and policies and promote learning, we suggest incorporating our ADAptation plan Quality Assessment indices into the portfolio of adaptation progress assessments and tracking methodologies.
Keywords: 320